2018
DOI: 10.1097/jtn.0000000000000362
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dwell Time for Peripheral Intravenous Catheters Started in the Field for Geriatric Blunt Trauma Patients

Abstract: Replacement time for peripheral intravenous (PIV) catheters started in the field is unclear. The purpose of this study was to compare field-start PIV catheter dwell time of 2 days or less versus field-start PIV catheter dwell time of more than 2 days for the development of indicators of infection for geriatric blunt trauma patients. A retrospective case series was conducted at the state-designated trauma referral center. Activated trauma team patients with blunt injury were included if 65 years or older and if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The median survival time of PIVC was 59.58 h, and the cumulative survival rates of 48 h, 72 h, and 96 h were 77.00%, 51.33%, and 20.33%, respectively. The survival rate of PIVC dropped rapidly after 60 h, with a cumulative survival rate of 51.33% at 72 h and a cumulative survival rate of 20.33% at 96 h. Therefore, it is reasonable to consider removing the catheter at 96 h. The dwelling time of the PIVC from Wei et al 19 and Day and Conde 20 are consistent with that found in this study.…”
Section: Discussionsupporting
confidence: 88%
“…The median survival time of PIVC was 59.58 h, and the cumulative survival rates of 48 h, 72 h, and 96 h were 77.00%, 51.33%, and 20.33%, respectively. The survival rate of PIVC dropped rapidly after 60 h, with a cumulative survival rate of 51.33% at 72 h and a cumulative survival rate of 20.33% at 96 h. Therefore, it is reasonable to consider removing the catheter at 96 h. The dwelling time of the PIVC from Wei et al 19 and Day and Conde 20 are consistent with that found in this study.…”
Section: Discussionsupporting
confidence: 88%